The Effectiveness of Audio-visual Media to Improve Students’ Writing Ability of Procedure Text - Masfa Maiza; Kunto Nurcahyoko (STKIP Al Hikmah Surabaya, 2020)
As writing is regarded as the most difficult skill, it is very challenging for teachers to teach writing. In order to conduct a good writing class, the application of media can be one of the alternative ways. This study examines the effectiveness of using audio-visual media to write a procedure text. This is a quasi-experimental study. The population of this study was the ninth graders of MTs Negeri 1 Landak and the sample was the students of IX-A and IX-B. The method of collecting data was test and field note, while t-test was used to analyze the data. The analysis of writing test uses the components of writing namely organization, grammar and mechanics. The result shows that the students’ average of experimental group is higher that control group and the result of t-test gains that tvalue > ttable = 7.05 > 1.99. In addition, the use of media also could improve the students’ writing ability. Finally, this media is effective to use in writing procedure text and the use of media would be useful for teachers and students.